Pengaruh Kualitas Pelayanan terhadap Keputusan Konsumen Berbelanja di Indomaret Sudirman 32 Pekanbaru - Zulfitri, Zulfitri; Lingga Pandu Winata (Lembaga Anotero Scientific, 2021)
This study is aimed at recognizing the impact the quality of servise has on The purcase of costumer indomaret sudirman 32 pekanbaru. Data analysis techniques using simple linear regression methods with quantitative approach. Research shows that the quality of service a positive influence on the consumer decision of shopping at indomaret sudirman 32 pekanbaru. The quality of service has a positive effect on decisions the purchase of consumer shoppers at the inomaret sudirman 32 pekanbaru.the value of this servise value is 5,190 > ttabel 1,991. Respondents give a value of 3,75 on the quality of service givenby indomaret sudirman 32 pekanbaru with the highest as 3,91 and the lowest we have an average of 3,60. Decision purchases made by the government consumers depend heavily on the quality of servise at the rate of attaiment the highest respondents at 4,60 and the lowest kritenia were gained by 3.92.